2013
DOI: 10.1007/s00059-013-3756-8
|View full text |Cite
|
Sign up to set email alerts
|

Bei QT-Intervall-Verlängerung im EKG-Verlauf bei Takotsubo-Kardiomyopathie droht prädisponierten Patienten eine Torsade de pointes

Abstract: We report the case of a female patient with congenital complete atrioventricular block who developed torsade de pointes (TdP) in the course of takotsubo cardiomyopathy. On the basis of this case, we show that the electrocardiographic evolutionary changes with QT interval prolongation (in the course of takotsubo cardiomyopathy) may be a TdP threatening period in patients with underlying predispositions. After reviewing the literature, we also present the electrocardiographic similarities between takotsubo cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Several cases have reported that QT interval prolongation could be related to pheochromocytoma,5)6)7) and we also experienced a 48-year-old pheochromocytoma woman with marked QT interval prolongation (Fig. 1A) that progressed to torsades de pointes (Fig.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Several cases have reported that QT interval prolongation could be related to pheochromocytoma,5)6)7) and we also experienced a 48-year-old pheochromocytoma woman with marked QT interval prolongation (Fig. 1A) that progressed to torsades de pointes (Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Electrocardiographic abnormalities that include rhythm, conduction and repolarization may occur in patients with pheochormocytoma. 25) 26) Several cases have reported that QT interval prolongation could be related to pheochromocytoma, 5) 6) 7) and we also experienced a 48-year-old pheochromocytoma woman with marked QT interval prolongation ( Fig. 1A ) that progressed to torsades de pointes ( Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Takotsubo cardiomyopathy is another candidate because it can prolong QT and cause TdP [ 10 ]. The suggested mechanism of QT elongation in Takotsubo cardiomyopathy is catecholamine or autonomic effects on the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…23 Several cases in literature have reported the relation of QT interval prolongation with pheochromocytoma. [24][25][26] Electrocardiographic abnormalities including rhythm, conduction and repolarization can occur in patients with pheochormocytoma. 27,28 They include marked prolongation of the Q-T interval and deep and wide symmetrically inverted T waves that are observed in 15% patients.…”
Section: Discussionmentioning
confidence: 99%